Overview of the Accuracy and Completeness of Diagnosis and Procedure Coding for Diabetes Mellitus Cases at Hospital X - Ari Sukawan; Ida Sugiarti; Gugun Priyadi; Ayu Rahayu; Diana Barsasella (Media Informasi, 2026)
Background: Complete and accurate medical records are a crucial component in supporting the accuracy of diagnosis coding, particularly for chronic diseases such as Diabetes Mellitus (DM). Incomplete data in medical records can lead to errors in diagnosis coding, which subsequently affects patient management and the quality of healthcare services. Objectives: This study aims to analyze the relationship between the completeness of medical record documentation and the accuracy of DM diagnosis coding at Hospital X. Methods: This study used a quantitative analytical observational design with a cross-sectional approach through observation and analysis of medical record documents. Statistical analysis was performed using the Chi-square test to determine the relationship between documentation completeness and coding accuracy. Results: From 66 medical record samples, it was found that 40 medical records (60.6%) had incomplete diagnosis documentation, while only 26 medical records (39.4%) were completely filled out. Furthermore, the accuracy of diagnosis code assignment also showed suboptimal results, with 42 medical records (63.6%) displaying incorrect code assignment, and only 24 medical records (36.4%) being coded accurately. The findings indicate that complete medical records tend to result in more accurate diagnosis coding. Conclusion: In conclusion, the completeness of medical records has a positive effect on the accuracy of DM diagnosis codes. Therefore, strengthening documentation practices, implementing standard operating procedures (SOPs), and providing regular coding training for medical record personnel are necessary to improve diagnosis coding accuracy and hospital data quality.